Insights into rumen microbial biosynthetic gene cluster diversity through genome-resolved metagenomics - Christopher L. Anderson (Nature Portfolio, 2021)
Anderson and Fernando use metagenomic binning approaches to reconstruct 2,809 microbial metagenome-assembled genomes from ruminants, and perform phylogenomic analyses on the biosynthetic gene clusters from over 8,000 total rumen microbial genomes. These genomes provide insight into the relationship between microbial populations and the production of secondary metabolites that may be important for manipulating rumen fermentation.